Does different cranial suture synostosis influence orbit volume and morphology in Apert syndrome?. Issue 3 (March 2022) - Lu, X.; Forte, A.J.; Alperovich, M.; Alonso, N.; Persing, J.A.
Abstract: This study was performed to compare the orbital and peri-orbital morphological variations in Apert syndrome patients with different cranial vault suture synostosis, so as to provide an anatomic basis for individualized surgical planning. Computed tomography scans of 57 unoperated Apert syndrome patients and 59 controls were subgrouped as follows: type I, bilateral coronal synostosis; type II, pansynostosis; type III, perpendicular combinations of cranial vault suture synostoses. Orbit bony cavity volume was significantly reduced in type I and type II, by 19% ( P  < 0.001) and 24% ( P  < 0.001), respectively. However, the reduction of orbital cavity volume in type III did not reach statistical significance. Globe volume projection beyond the orbital rim, however, increased by 76% ( P  < 0.001) in type III, versus an increase of 54% ( P  < 0.001) in type I and 53% ( P  < 0.001) in type II, due to different ethmoid and sphenoid bone malformations. Maxillary bone volume was only significantly reduced in type I bicoronal synostosis (by 24%, P  = 0.048). Both type I and type II developed relatively less zygoma and sphenoid bone volume. Different cranial vault suture synostoses have varied influence on peri-orbital development in Apert syndrome. Instead of mitigating the abnormalities resulting from bicoronal synostosis in type I, additional midline suture synostosis worsens the exorbitism due to a more misshaped ethmoid.